Education On The Impact Of Gadget Use On Children's Health At SDN 2 Wonorejo Karanganyar - solikah, siti nur (Universitas Borneo Tarakan, 2024)
Technology is increasingly developing day by day following the development of world globalization. Gadgets as a communication tool are experiencing rapid development. Since Covid-19, gadgets have become children's friends in everyday life. Uncontrolled use of gadgets causes various health problems in children, such as decreased eye sharpness, behavioral disorders, social, emotional and psychological disorders in children. Education about the impact of gadget use on children is important to improve the level of health of children in Indonesia so that they grow and develop well in the future as a generation of the nation. The aim of this activity is to increase the knowledge and understanding of students at SDN 2 Wonorejo Karangayar regarding the impact of using gadgets on children's health. The implementation method was carried out using the health education method in the form of presentation of material and questions and answers targeting 23 elementary school age children. Based on the analysis of pre and post-test data, there was an increase in the average understanding of students in receiving information from the extension team. The recommendation for follow-up to this activity is that teachers coordinate with all parents in assisting them in using gadgets while at home and at school so that they do not affect children's health, so that optimal levels of children's health are achieved. Keywords: education, gadgets, health, children